2009
DOI: 10.1158/0008-5472.can-08-2473
|View full text |Cite
|
Sign up to set email alerts
|

A Requirement for Cyclin-Dependent Kinase 6 in Thymocyte Development and Tumorigenesis

Abstract: Cyclin-dependent kinase 6 (CDK6) promotes cell cycle progression and is overexpressed in human lymphoid malignancies. To determine the role of CDK6 in development and tumorigenesis, we generated and analyzed knockout mice. Cdk6-deficient mice show pronounced thymic atrophy due to reduced proliferative fractions and concomitant transitional blocks in the double-negative stages. Using the OP9-DL1 system to deliver temporally controlled Notch receptordependent signaling, we show that CDK6 is required for Notch-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
130
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 38 publications
(57 reference statements)
7
130
0
2
Order By: Relevance
“…Interestingly, Cdk2 or cyclin A2-associated kinase activities were elevated compared with control and extended from 18 to 72 h (Fig. 4A, third and fourth gels from the top, lanes [8][9][10][11][12]. This result indicates that Cdk1 might be responsible for suppressing Cdk2/ cyclin A2 kinase activity at the end of S phase in wild-type cells, which prevents re-replication from occurring and was confirmed by silencing of Cdk2 (Fig.…”
Section: Cdk1 Is Essential For Cellular Proliferation and Early Embrymentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly, Cdk2 or cyclin A2-associated kinase activities were elevated compared with control and extended from 18 to 72 h (Fig. 4A, third and fourth gels from the top, lanes [8][9][10][11][12]. This result indicates that Cdk1 might be responsible for suppressing Cdk2/ cyclin A2 kinase activity at the end of S phase in wild-type cells, which prevents re-replication from occurring and was confirmed by silencing of Cdk2 (Fig.…”
Section: Cdk1 Is Essential For Cellular Proliferation and Early Embrymentioning
confidence: 64%
“…In contrast, there was no detectable Cdk1 or cyclin B1-associated kinase activity at any of the time points in Cdk1 NULL cells (Fig. 4A, top two gels, lanes [7][8][9][10][11][12]. This finding suggests that cyclin B1 does not form active complexes with Cdk2 despite its increased association in Cdk1 NULL cells ( Fig.…”
Section: Cdk1 Is Essential For Cellular Proliferation and Early Embrymentioning
confidence: 89%
See 1 more Smart Citation
“…Among them is the ability of CDK6 to modulate differentiation in specific cell types including murine erythroid leukemia, primary mouse astrocytes, osteoblasts and osteoclasts, thymocytes, neurons, cardiomyocytes and hematopoietic cells. [22][23][24][25][26][27][28][29][30][31] In hematopoietic cells, for example, down-regulation of CDK6 allows terminal differentiation due to the release of runt-related transcription factor 1 (Runx1), a transcriptional factor required for the opening of chromatin of important hematopoietic regulator genes. 27 Location of CDK6 CDK6 has been shown to reside in the cytoplasm of many cell types.…”
Section: Introductionmentioning
confidence: 99%
“…64 In another study, CDK6-deficient mice were shown to be resistant to the development of lymphoma. 30 Similarly, CDK6 knock-out mice were also resistant to neurogenic locus notch homolog protein 1 (NOTCH1) driven T-cell acute lymphoblastic leukemia (T-ALL). Inhibition of CDK6-cyclin D3 by PD0332991 in human leukemic cells causes apoptosis in addition to cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%